Method for producing metal nitride

By molding raw material powder at a 40-70% gap rate and using an insulation layer, the method addresses issues of unstable combustion and low recovery in metal nitride production, achieving improved yield and reduced powder generation.

JP7623955B2Active Publication Date: 2025-01-29TOKUYAMA CORP
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2021562696
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-12-05
Filing Date
2020-12-02
Publication Date
2025-01-29
Estimated Expiration
2040-12-02

AI Technical Summary

Technical Problem

Conventional methods for producing metal nitride, such as silicon nitride, face issues with high nitrogen reaction pressures leading to unstable combustion heat propagation, microcracks in the reaction container, and low recovery rates due to unreacted raw materials, resulting in decreased yields and increased powder generation.

Method used

The method involves molding raw material powder into a specific gap rate of 40-70% and forming an insulation layer with nitrogen permeability to control the combustion synthesis, reducing the risk of microcracks and improving recovery rates by ensuring complete reaction.

Benefits of technology

This approach effectively suppresses powder generation and enhances the recovery rate of metal nitride by ensuring complete combustion and easy handling, while maintaining the integrity of the molded bodies during the reaction process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007623955000002
    Figure 0007623955000002
  • Figure 0007623955000003
    Figure 0007623955000003
  • Figure 0007623955000004
    Figure 0007623955000004
Patent Text Reader

Abstract

This metal nitride production method is characterized in that a starting material powder, which includes a metal powder, held in a reaction vessel (2) is ignited in a nitrogen atmosphere, and the heat from the nitriding combustion of the metal powder is allowed to propagate throughout the entirety of the starting material powder held in the vessel to synthesize a metal nitride. The starting material powder is held in the reaction vessel (2) in the form of shaped bodies (1B) with a void ratio of 40 to 70%. The present invention can provide a metal nitride production method which can suppress the occurrence of powder scattering so as to improve the metal nitride collection rate.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a metal nitride. [Background technology]

[0002] Metal nitrides such as silicon nitride, aluminum nitride, and boron nitride have attracted attention as ceramic raw materials for various industrial materials because sintered bodies thereof generally have excellent properties such as high thermal conductivity, high insulation properties, and high strength. Silicon nitride sintered bodies, which are made by adding various sintering aids to silicon nitride powder and sintering them at high temperatures, are characterized by their light weight, high mechanical strength, high chemical resistance, high electrical insulation, etc., among various ceramic sintered bodies, and are used as wear-resistant parts such as ball bearings and high-temperature structural parts. In addition, by optimizing the type of aid and sintering conditions, it is possible to increase thermal conductivity, so they have also come to be used as thin, high-strength heat-dissipating substrate materials.

[0003] As a method for producing silicon nitride powder, a method for synthesizing silicon nitride by a direct nitridation method using a self-propagating high temperature synthesis (SHS) method is known as a conventional technique (see, for example, Patent Document 1, Examples 3 and 4). The self-propagating method uses silicon powder as a raw material, ignites a portion of the raw material powder under a nitrogen atmosphere, and carries out a synthesis reaction by the self-heating of the raw material compound. Example 3 of this Patent Document 1 does not disclose the purity of the starting material or detailed manufacturing conditions, but describes that a carbon crucible filled with silicon powder having an average particle size of 20 μm was placed in a reaction vessel, and the silicon powder was irradiated with a YAG laser at an output of 20 W in a nitrogen atmosphere at 5 atmospheres to ignite it, and then the laser irradiation was stopped. A combustion synthesis reaction was then carried out by the subsequent self-heating, and a fine powder product was obtained. Furthermore, in Example 4 of Patent Document 1, the purity of the starting material or detailed manufacturing conditions are not described either, but it is described that a carbon crucible filled with silicon powder having an average particle size of 5 μm was placed in a reaction vessel, and the silicon powder was irradiated with a YAG laser at an output of 100 W in a nitrogen atmosphere at 30 atmospheres to ignite it, and then the laser irradiation was stopped, and a combustion synthesis reaction was carried out by the subsequent self-heating, resulting in the production of a fine powder product.

[0004] The method of producing silicon nitride by the direct nitridation method using self-heating described above is extremely advantageous in terms of thermal energy, but in the method of Patent Document 1, the nitridation reaction pressure is too high, causing an explosive chain reaction, and the fine silicon nitride particles produced are fused together, resulting in less production of fine particles essential for obtaining a dense sintered body. For this reason, it is difficult to obtain a dense sintered body with the silicon nitride powder obtained by this method, and the problem of a large shrinkage rate during sintering has not been improved.

[0005] Furthermore, when the combustion synthesis reaction is carried out by self-heating caused by igniting silicon powder as described above, the raw material silicon powder is heated all at once and the reaction proceeds, which may cause melting and fusion of silicon during the reaction. For this reason, in Patent Document 2, silicon nitride powder is mixed as a diluent into the raw material silicon powder in an amount of 10 mass% or more, and the bulk density of the powder layer (raw material powder layer) consisting of the mixture of the silicon powder and the diluent is set to 0.3 to 0.65 g / cm. 3 It has been proposed to carry out combustion synthesis by adjusting the diluent to a level that allows the combustion reaction to proceed mildly and prevents melting and fusion of silicon, and by adjusting the bulk density of the raw material powder layer to a certain degree, it is possible to prevent the resulting silicon nitride chunks from hardening and agglomerating, making them easier to pulverize. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2000-264608 A [Patent Document 2] WO2018 / 110565 publication Summary of the Invention [Problem to be solved by the invention]

[0007] However, in the conventional method for producing silicon nitride powder, when the raw material powder is filled into the reaction vessel, powdering may occur, which may deteriorate the working environment. In addition, when the reaction vessel is installed in the reaction vessel and the air in the reaction vessel is replaced with nitrogen gas, the pressure change in the reaction vessel promotes the filling of the raw material powder, which may cause cracks in the filled raw material powder. If cracks occur in the filled raw material powder, the propagation of the nitriding combustion heat becomes unstable, and there is a risk that unreacted raw material will remain in the cracked area. If unreacted raw material remains in the cracked area, much of the generated metal nitride will also be removed when the unreacted raw material is removed by brushing or the like, resulting in a decrease in the recovery rate of the metal nitride.

[0008] Therefore, an object of the present invention is to produce a metal nitride which can suppress the generation of powder and improve the recovery rate of the metal nitride. [Means for solving the problem]

[0009] The inventors conducted numerous experiments and investigations into the production of silicon nitride powder by a direct nitridation method utilizing self-combustion (hereinafter also referred to as the combustion synthesis method), and as a result discovered the new fact that by producing metal nitrides using compacts obtained by molding raw material powders, it is possible to suppress the generation of powdering and also to suppress cracking of the raw material powder, thereby improving the recovery rate of metal nitride, which led to the completion of the present invention. As described in the above-mentioned Patent Document 2 and the like, it has been common to perform combustion synthesis by reducing the bulk density of the raw material powder to a certain degree. According to such technical common sense, if the raw material powder is molded to increase the bulk density, there is a concern that the combustion heat in the combustion synthesis method will be difficult to propagate and that the generated chunks of silicon nitride will become impossible to crush. However, contrary to expectations, it has been found that by using a specific molded body made of the raw material powder of the present invention, it is possible to produce metal nitrides by the combustion synthesis method, and the use of a molded body makes it possible to suppress the generation of dust.

[0010] That is, according to the present invention, The present invention provides a method for producing metal nitrides, which comprises igniting raw material powder, including a metal powder, contained in a reaction vessel under a nitrogen atmosphere and propagating the nitriding combustion heat of the metal powder throughout the contained raw material powder, thereby synthesizing a nitride of the metal, characterized in that the raw material powder is contained in the reaction vessel as a compact having a porosity of 40 to 70%.

[0011] In the production method of the present invention, the following aspects can be suitably adopted. (1) The raw material powder contains 0 to 80 parts by mass of a metal nitride powder with respect to 100 parts by mass of the metal powder. (2) A plurality of compacts of the raw material powder are placed in contact with one another in the reaction vessel. (3) A heat insulating layer made of a material that is nitrogen permeable and inert to the nitriding reaction is formed and adhered to the upper surface of the compact of the raw material powder contained in the reaction vessel. (4) The metal is silicon. Effect of the Invention

[0012] According to the present invention, it is possible to provide a method for producing a metal nitride, which can suppress the generation of powder and improve the recovery rate of the metal nitride. [Brief description of the drawings]

[0013] [Figure 1]FIG. 1 is a schematic diagram showing an example of the arrangement of molded bodies in a reaction vessel. [Diagram 2] FIG. 2 is a schematic diagram showing an example of the arrangement of the molded bodies in the reaction vessel. [Diagram 3] 3(a) to (c) are schematic diagrams each showing an example of the arrangement of molded bodies in a reaction vessel. [Figure 4] FIG. 4 is a schematic diagram showing an example of the arrangement of the molded bodies in the reaction vessel. [Diagram 5] FIG. 5 is a schematic diagram showing an example of a heat insulating layer formed above a molded body. [Figure 6] FIG. 6 is a schematic diagram showing an example of heat insulating layers formed above, below and on the sides of the molded body. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] The method for producing metal nitrides of the present invention is a method for producing metal nitrides, in which raw powders including metal powders contained in a reaction vessel are ignited under a nitrogen atmosphere, and the heat of nitriding combustion of the metal powder is propagated to the entire raw powder contained therein to synthesize metal nitrides. The method for producing metal nitrides of the present invention is characterized in that the raw powders are contained in the reaction vessel as a compact having a porosity of 40 to 70%. This makes it possible to suppress the generation of powdering and improve the recovery rate of the metal nitrides. Hereinafter, this production method will be described in detail.

[0015] (Raw material powder) In the present invention, the raw material powder includes a metal powder. Examples of the metal powder include silicon powder, aluminum powder, and boron powder. Although silicon and boron are nonmetallic elements, silicon alone may be called metallic silicon, and boron alone may be called metallic boron. Therefore, in this specification, silicon powder and boron powder are also included in the metal powder. Silicon powder is particularly suitable for the present invention.

[0016] In addition, the above metal powder contained in the raw material powder has an average particle size D 50In order to obtain a molded product having a porosity of 40 to 70%, it is preferable that the average particle size D is in the range of 1 to 10 μm. 50 refers to the particle size when the cumulative volume in the particle size distribution measured by the laser diffraction scattering method is 50%.

[0017] In relation to the above, the metal powder used as the raw material powder is preferably a high-purity metal powder. For example, when the metal powder is silicon powder, the Al and Fe contents are preferably 200 ppm or less, respectively. When the metal powder is aluminum powder, the Si and Fe contents are preferably 200 ppm or less, respectively. Furthermore, when the metal powder is boron powder, the Fe content is preferably 200 ppm or less. If such metal elements are present, the sinterability of the obtained metal nitride may decrease, and the properties such as the strength of the obtained sintered body may decrease. For the same reason, it is preferable that the content of high-melting point metals such as W and Mo is also 200 ppm or less.

[0018] It is preferable that the surface of the metal powder is moderately oxidized. That is, the oxide film formed on the surface of the metal powder is an important factor for appropriately controlling the progress of the combustion synthesis reaction. As a method for moderately oxidizing the surface, a method of pulverizing the powder to the above-mentioned particle size range in air is adopted as a simple method. For example, a jet mill using air is preferably adopted. The degree of oxidation of the metal powder may be appropriately determined within a range that does not inhibit the combustion synthesis reaction of the present invention, but it is preferable to contain oxygen in an amount of about 0.1 to 1 mass% with respect to the weight of the metal powder. If the amount of oxygen in the metal powder is less than the above range, the combustion temperature during the nitriding reaction tends to be excessively high, and if the amount of oxygen is more than this range, the nitriding reaction tends to be suppressed, and problems such as poor ignition and residual unreacted metal may occur.

[0019] In the present invention, the above-mentioned metal powder used as the raw material powder may be obtained in any manner, but it is preferable that the purity and particle size are adjusted to the above-mentioned predetermined range. For example, when the metal powder is silicon powder, it is generally economical to recover and use the fine powder generated in the process of crushing a semiconductor polycrystalline silicon rod to manufacture nuggets. In addition, commercially available industrial raw materials can be crushed and used.

[0020] The raw material powder may contain a diluent. The reaction between the metal powder and nitrogen is an exothermic reaction, and the surface reaction is a rate-limiting reaction, so the greater the amount of metal powder, the more difficult it is to control the temperature of the raw material powder. However, by making the raw material powder contain a diluent, the content of the metal powder in the raw material powder is reduced, and the heat generation of the raw material powder is also reduced. This makes it easier to control the temperature of the raw material powder. The diluent is preferably a metal nitride powder, and in particular, in order to avoid the need to remove the diluent contained in the raw material powder from the generated metal nitride after the metal powder reacts to generate the metal nitride, the metal nitride powder used as the diluent is preferably a nitride powder of the same metal element as the raw material metal powder. For example, when the metal powder is silicon powder, the metal nitride powder used as the diluent is preferably silicon nitride, when the metal powder is aluminum powder, the metal nitride powder used as the diluent is preferably aluminum nitride, and when the metal powder is boron powder, the metal nitride powder used as the diluent is preferably boron nitride. For example, the metal nitride produced by the method for producing metal nitride of the present invention can be used as these diluents.

[0021] The raw powder preferably contains 0 to 80 parts by mass of metal nitride with respect to 100 parts by mass of metal powder. That is, the raw powder may or may not contain metal nitride. When the raw powder contains metal nitride, the content of the metal nitride is preferably 80 parts by mass or less with respect to 100 parts by mass of metal powder. When the content of the metal nitride is 80 parts by mass or less with respect to 100 parts by mass of metal powder, the compact can be easily ignited under a nitrogen atmosphere, and the nitriding combustion heat of the metal can be easily propagated to the entire compact contained in the reaction vessel. From this viewpoint, the content of the metal nitride is more preferably 50 parts by mass or less, and more preferably 30 parts by mass or less with respect to 100 parts by mass of metal powder. In addition, from the viewpoint of controlling the temperature of the raw powder, the content of the metal nitride is more preferably 1 part by mass or more, and more preferably 5 parts by mass or more with respect to 100 parts by mass of metal powder.

[0022] The raw material powder may contain other components other than the metal powder and the diluent used as necessary, as long as the effects of the present invention are not impaired. Examples of other components include chlorides such as sodium chloride and ammonium chloride, and oxides such as calcium oxide, yttrium oxide, and magnesium oxide. The amount of other components is preferably 10% by mass or less, more preferably 5% by mass or less, even more preferably 1% by mass or less, and even more preferably 0% by mass, based on the total amount of the raw material powder.

[0023] (Molded body) The porosity of the molded body is 40 to 70%. If the porosity of the molded body is less than 40%, the permeation of nitrogen gas into the molded body may be insufficient. In this case, the combustion reaction does not proceed sufficiently, and the amount of unreacted material increases due to an extinguishment during the reaction, resulting in a decrease in yield. In addition, if the porosity of the molded body is greater than 70%, the strength of the molded body required for handling the molded body may not be ensured. From these viewpoints, the porosity of the molded body is preferably 48 to 68%, more preferably 50 to 65%. Conventionally, it was thought that the combustion reaction did not proceed sufficiently when the raw material powder was molded into a molded body. However, as a result of intensive research by the present inventors, it was found that the combustion reaction proceeds sufficiently even in the case of a molded body by making the porosity of the molded body 40% or more. The porosity of the molded body can be controlled by adjusting the average particle size of the raw material powder, the molding pressure during molding, etc.

[0024] When a plurality of molded bodies are contained in the reaction vessel, the average value of the porosities of the plurality of molded bodies is regarded as the porosity of the molded body in the present invention. Here, the average value of the porosities of the plurality of molded bodies is a weighted average value calculated from the porosities of the individual molded bodies and the weights of the individual molded bodies. Therefore, when multiple molded bodies are used, the porosity of some of the molded bodies may be less than 40% or more than 70%, but it is preferable that the porosity of each individual molded body in the multiple molded bodies is all 40 to 70%, more preferably 48 to 68%, and even more preferably 50 to 65%.

[0025] The porosity of the green body can be calculated from the density of the green body when no voids are present (theoretical density of the green body: D2) and the measured density of the green body (density of the green body: D1) as follows, and in detail, is measured by the method described in the Examples. The theoretical density of the green body can be obtained from the density and component ratio of each raw material constituting the green body. Porosity (%)=(1-D1 / D2)×100

[0026] The bulk density of the molded body is preferably 0.85 to 1.30 g / cm 3 The bulk density of the compact is 0.85 g / cm3 When the bulk density of the molded body is 1.30 g / cm or more, the strength of the molded body required for handling can be ensured. 3 If the bulk density is less than 0.90 g / cm, nitrogen gas can be sufficiently permeated into the molded body. This allows the nitriding combustion reaction to proceed sufficiently. From this viewpoint, the bulk density of the molded body is more preferably 0.90 to 1.20 g / cm. 3 and more preferably 0.95 to 1.15 g / cm 3 It is.

[0027] The shape of the molded body is not particularly limited. Examples of the shape of the molded body include a plate shape, a rectangular parallelepiped, a cube, a cylindrical shape, a prismatic shape, a spherical shape, and an elliptical spherical shape. The molded body accommodated in the reaction vessel may be a single molded body or a plurality of molded bodies. When a plurality of molded bodies are accommodated in the reaction vessel, the shape of the molded body is preferably a shape that allows the molded bodies to contact each other, and is preferably a shape that allows the molded bodies to come into surface contact with each other. This allows the nitriding combustion heat to be easily propagated between the molded bodies. From this viewpoint, the shape of the molded body is preferably a cylindrical shape, a prismatic shape, and the like, and among them, in consideration of the ease of molding, a cylindrical shape is more preferable.

[0028] The molding method of the raw material powder is not particularly limited as long as it can produce a molded body of the raw material powder. However, in order to suppress the inclusion of oxygen impurities in the raw material powder, it is preferable to mold the raw material powder by dry molding. For example, the raw material powder may be molded by a uniaxial pressure molding method. In this case, for example, the raw material powder can be molded using an automatic dry press molding machine. The raw material powder may also be molded by compression granulation such as briquetting and tableting.

[0029] (Placement of Molded Body in Reaction Vessel) Instead of filling the raw powder directly into a heat-resistant container, the raw powder can be stored in a reaction container as a molded body, thereby preventing the raw powder from scattering. This prevents the work environment from deteriorating due to the generation of powder. As an example of the reaction container, a graphite reaction container can be used. In addition, since the density of the molded body hardly changes due to the change in pressure inside the reaction container when the air inside the reaction container is replaced with nitrogen gas, the generation of cracks in the raw powder can be prevented. The way in which the molded body is stored in the reaction container is not particularly limited as long as the molded body can be stored in the reaction container to a certain degree of density. For example, as shown in FIG. 1, a single plate-shaped molded body 1A may be stored in the reaction container 2. In addition, as shown in FIG. 2, a plurality of cylindrical molded bodies 1B may be stored in the reaction container 2 in a state where they are stacked without contacting adjacent molded bodies 1B in the left-right direction. Furthermore, as shown in FIG. 3(a), the molded bodies 1B stored in the reaction container may be stacked flat with adjacent molded bodies 1B in contact with each other in the left-right direction. In addition, as shown in Fig. 3(b), a method of stacking a plurality of cylindrical molded bodies 1B may be such that a molded body 1B is stacked above a molded body 1B so as to overlap only one molded body 1B while being in contact with adjacent molded bodies 1B in the left-right direction. Furthermore, as shown in Fig. 3(c), a molded body 1B may be stacked above a molded body 1B so as to overlap two molded bodies 1B while being in contact with adjacent molded bodies 1B in the left-right direction. In addition, as shown in Fig. 4, a plurality of spherical molded bodies 1C may be placed in a reaction vessel 2 in a filled state.

[0030] When multiple molded bodies of the raw material powder are accommodated in a heat-resistant vessel, the distance between each molded body and the other molded body located nearest thereto is preferably within 10 mm, more preferably within 5 mm, and further preferably the multiple molded bodies are accommodated in the reaction vessel in contact with each other, so that the nitriding combustion heat can be easily propagated between adjacent molded bodies. When two adjacent molded bodies are in contact with each other, from the viewpoint of more reliably transmitting the heat of nitriding combustion between the molded bodies, the two adjacent molded bodies are preferably in point contact, more preferably in line contact, and even more preferably in surface contact. Also, a molded body may be in surface contact with an adjacent molded body and in surface contact with another adjacent molded body. Furthermore, when two adjacent molded bodies are in surface contact, the contact area between the two adjacent molded bodies (contact area between the molded bodies) is preferably 1 cm or less. 2 More preferably, it is 2 cm or more. 2 The contact area between two adjacent molded bodies is an average value, and can be calculated from the total number of contact points between the molded bodies and the total number of contact areas between the molded bodies.

[0031] As shown in Fig. 5, a heat insulating layer 3 made of a material that is nitrogen permeable and inactive to the nitriding reaction may be formed in close contact with the upper surface of the molded body 1B of the raw material powder contained in the reaction vessel 2. This makes it possible to suppress the dissipation of nitriding combustion heat from above the molded body, and to prevent the temperature of the molded body present at the top among the molded bodies contained in the reaction vessel from decreasing to a temperature that is insufficient for the molded body to react with nitrogen gas. This also makes it possible to suppress the remaining of unreacted materials.

[0032] The heat insulating layer 3 can be formed, for example, from a powder of a nitride of the same metal element as the metal powder in the compact. For example, when the metal powder in the compact is silicon powder, the heat insulating layer is preferably silicon nitride powder. The heat insulating layer formed from silicon nitride powder has nitrogen permeability and is inactive against nitriding reaction. Also, graphite fiber, porous ceramic plate, etc. may be used as the heat insulating layer. When the heat insulating layer is a powder of a metal nitride, some dusting occurs, but the dusting is suppressed compared to when the raw material powder is filled into the reaction vessel without being molded. Also, as shown in FIG. 6, the heat insulating layer 3 made of a material that has nitrogen permeability and is inactive against nitriding reaction may be formed not only above the compact 1B but also below and to the side. This can prevent deterioration of the reaction vessel and further suppress the reaction between the compact and the reaction vessel. For example, when the compact is in contact with the reaction vessel, if the reaction vessel is made of graphite, metal carbides may be formed on the contact surface of the compact with the reaction vessel, but the above-mentioned embodiment as shown in FIG. 6 can prevent the formation of metal carbides.

[0033] (Synthesis of metal nitrides) In the nitride manufacturing method of the present invention, raw material powder including metal powder contained in a reaction vessel is ignited in a nitrogen atmosphere, and the heat of nitriding combustion of the metal powder is propagated throughout the raw material powder contained therein to synthesize metal nitride. An ignition agent containing powder of Ti, Al, etc. can be placed in the part that serves as the ignition point during the combustion synthesis reaction. For example, a part of the compact is hollowed out to make a depression. An ignition agent can be placed in the depression. The amount of ignition agent placed in the compact should be small enough that it does not affect the sinterability of the resulting metal nitride. When an ignition agent is placed, it can be placed at one or more locations, either at the end or center of the compact, or at any other location.

[0034] After the compacts are placed in a reaction vessel, the atmosphere in the reaction vessel is replaced with nitrogen, and the compacts are ignited under a nitrogen atmosphere. The reaction vessel is generally placed in a pressure-resistant sealed reactor having an ignition device and a gas supply and exhaust mechanism, and the heat-resistant reactor is depressurized to remove air, and then nitrogen gas is supplied to replace the atmosphere.

[0035] In the present invention, the reaction may be carried out under normal pressure or under pressure, but it is preferable to carry out the reaction under pressure. In particular, when carrying out a reaction to obtain silicon nitride as a metal nitride, it is preferable to carry out the reaction under pressure from the viewpoint of facilitating the progress of the nitriding reaction. Specifically, it is preferable to carry out the reaction under a pressure of normal pressure to 1 MPa, and such a pressure is achieved by the nitrogen pressure supplied to the closed reactor. If the pressure in the closed reactor is lower than the above range, the yield tends to decrease due to a large amount of unreacted material caused by fire during the reaction, etc., and if the pressure in the closed reactor is higher than the above range, the reaction temperature tends to increase excessively, producing coarse silicon agglomerates, or the silicon nitride powder finally obtained tends to contain many coarse particles that are difficult to pulverize, making it difficult to ensure an appropriate particle size distribution.

[0036] In the present invention, it is preferable to ignite the above-mentioned compact and directly react the metal powder by self-combustion and diffusion while the compact is still pressurized with nitrogen, that is, in a nitrogen atmosphere of normal pressure to 1 MPa. Ignition can be carried out by a conventionally known method, for example, ignition by arc discharge using a pair of electrodes attached to a closed reactor, ignition by applying electrical current to a carbon or metal heater, ignition by laser irradiation, etc.

[0037] When ignited as described above, the compact is heated to a reaction temperature of, for example, 1500 to 2000°C, where the combustion synthesis reaction occurs directly between the metal powder and nitrogen, producing a metal nitride. The resulting metal nitride is usually an aggregate product (i.e., an aggregate of metal nitride).

[0038] (Crushing of metal nitrides) In the method for producing a metal nitride of the present invention, it is preferable to mechanically pulverize the metal nitride under a dry condition. In the present invention, a metal nitride is obtained by carrying out a combustion synthesis reaction as described above. As described above, the metal nitride obtained in this manner is usually in a lump shape. By mechanically pulverizing the lump metal nitride as described below, metal nitride particles having a small powder particle size and an appropriate particle size distribution can be obtained. In addition, the lump metal nitride is obtained from a molded body having a porosity of 40% or more, and therefore can be easily pulverized.

[0039] Mechanical grinding In the present invention, the metal nitride powder having an appropriate particle size distribution can be obtained by mechanically pulverizing the bulk metal nitride obtained by the above-mentioned combustion synthesis reaction. This mechanical pulverization is preferably performed by a dry method. In wet pulverization using a liquid medium such as water, the pulverization pressure is applied evenly, which is advantageous in obtaining fine powder. However, wet pulverization has a problem of low productivity. In addition, there is a possibility that impurities are generated by the reaction between the metal nitride and the liquid medium, and the impurities must be removed by purification such as acid treatment after pulverization. Moreover, in order to prevent an increase in the environmental load, it is necessary to treat the acid treatment waste liquid, which increases the cost of pulverization. For this reason, it is preferable to pulverize the bulk metal nitride obtained by the above-mentioned reaction of the present invention by dry pulverization.

[0040] It is also possible to obtain a metal nitride powder having an appropriate particle size distribution by carrying out multiple grinding processes under different grinding conditions of the lump metal nitride, preparing multiple types of ground products having different particle size distributions, and appropriately mixing these. It is also possible to obtain a metal nitride powder having an appropriate particle size distribution by introducing a classification process such as sieving.

[0041] Such dry grinding is carried out using grinding machines such as vibration mills, bead mills, and airflow grinding machines (jet mills) that collide materials to be crushed. An obvious measure to suppress heavy metal contamination during grinding is to use a metal nitride common material as the grinding media. For example, airflow grinding using a jet mill is most suitable from the viewpoint of preventing contamination, since it is possible to grind the powder by the collision of the powder with itself. Even in the method using a vibration mill or bead mill, there is no problem with contamination if balls made of a metal nitride common material are used as the grinding media. In this case, the grinding media also wears out, albeit to a small extent, so it is obvious that media with less contamination should be used.

[0042] Regarding the preparation of metal nitride balls for use as grinding media, the method of obtaining a sintered body resistant to wear using only metal nitride is expensive, so in order to prepare media at low cost, a method of mixing and sintering sintering aids such as yttria, magnesia, and alumina can also be adopted. The selection of these sintering aids is not problematic as a method of preparing metal nitride powder for sintered bodies as long as the components acceptable for the target metal nitride powder are selected. When grinding metal nitride powder using a vibrating mill or a bead mill in a dry manner, it is preferable to grind the powder by adding a small amount of alcohol such as ethanol or isopropyl alcohol, or water. These components function as grinding aids that promote grinding, so that the grinding time can be shortened. The amount of grinding aid to be added is within the range that the ground material can be kept dry. The amount of the grinding aid varies depending on the components, but is preferably in the range of 0.1 to 2 mass% with respect to the metal nitride powder to be ground.

[0043] (Production of Metal Nitride Sintered Body) The metal nitride powder obtained as described above can be used to produce a metal nitride sintered body by a known method. For example, when the metal nitride powder is silicon nitride powder, the silicon nitride powder is mixed with a sintering aid such as yttria, magnesia, zirconia, or alumina, and the mixture is pressed to produce a powder having a bulk density of 1.7 g / cm. 3 Above, especially 1.85g / cm 3More preferably, 1.95 g / cm 3 The above-mentioned molded body is then fired to obtain a sintered body.

[0044] The above press molding is typically uniaxial press molding, but a method in which uniaxial press molding is followed by CIP (Cold Isostatic Pressing) molding is preferably employed.

[0045] The firing is performed at 1700 to 2000°C in a nitrogen atmosphere. The density of the sintered body depends on both the firing temperature and the firing time. For example, when firing at 1700°C, the firing time is about 3 to 20 hours. When firing at a temperature of 1850°C or higher, if the firing time is too long, the density of the sintered body may decrease due to the decomposition of silicon nitride itself. In this case, the decomposition of the silicon nitride sintered body can be suppressed by sintering in an atmosphere pressurized with nitrogen. The higher the nitrogen pressure, the more the decomposition of silicon nitride can be suppressed, but for economic reasons such as the pressure resistance of the device, a pressure of less than 1 MPa is preferably adopted. In order to obtain a high-density sintered body with a relative density of 99% or more, it is preferable to carry out sintering in a pressurized nitrogen atmosphere at 1800° C. or more. The metal nitride sintered body obtained as described above can be suitably used as a heat dissipating substrate material, etc. EXAMPLES

[0046] EXAMPLES The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. In the examples, various physical properties were measured by the following methods.

[0047] (1) Presence or absence of powder The presence or absence of powdering when the molded bodies made of the raw material powders of each Example and the raw material powders of each Comparative Example were filled into a reaction vessel was confirmed. A: No dusting was observed. B Powdering was observed.

[0048] (2) Nitride recovery rate The mass of the silicon nitride block before brushing was W1, and the mass of the silicon nitride block after brushing to remove unreacted silicon was W2, and the nitride recovery rate was calculated from the following formula. The nitride recovery rate was evaluated according to the following criteria. Brushing was continued until no black areas (unreacted silicon) were visible on the surface of the silicon nitride block when observed with the naked eye. Nitride recovery rate (%) = W2 / W1 × 100 A. Nitride recovery rate is 95% or more B. Nitride recovery rate is less than 95%

[0049] (3) Particle size of silicon nitride powder Sample preparation As a pretreatment of the silicon nitride powder sample, the silicon nitride powder was calcined in air at a temperature of about 500°C for 2 hours. The calcination treatment may cause a particle size measurement in which the silicon nitride powder has a low surface oxygen content or the particle surface is covered with a hydrophobic substance due to a grinding aid during grinding, making the particles themselves hydrophobic. In such cases, dispersion in water may be insufficient, making it difficult to measure particle size reproducibly. Therefore, by calcining the silicon nitride powder sample in air at a temperature of about 200°C to 500°C for several hours, the silicon nitride powder is made hydrophilic, making it easier to disperse in water solvents and enabling highly reproducible particle size measurements. It has been confirmed that calcination in air has almost no effect on the particle size measured.

[0050] Particle size measurement 90 ml of water and 5 ml of sodium pyrophosphate with a concentration of 5% by mass were placed in a beaker (inner diameter 60 mmφ, height 70 mm) with a maximum marked capacity of 100 ml and stirred well, after which an earpick-sized amount of silicon nitride powder sample was added and the silicon nitride powder was dispersed for 2 minutes at AMPLITUDE 50% (approximately 2 amperes) using an ultrasonic homogenizer (Nippon Seiki Seisakusho US-300E, tip diameter 26 mm) The tip of the tip was inserted into the beaker up to the 20 ml mark during dispersion. Next, the particle size distribution of the obtained silicon nitride powder dispersion was measured using a laser diffraction / scattering particle size distribution measurement device (Microtrac MT3300EXII, manufactured by Microtrac-Bell Co., Ltd.). The measurement conditions selected were water (refractive index 1.33) as the solvent, refractive index 2.01 as the particle characteristics, transparent as the particle transparency, and non-spherical as the particle shape. The particle size at which the cumulative curve of the particle size distribution measured in the above particle size distribution measurement is 50% is defined as the average particle size.

[0051] (4) Porosity of the green body The density of each compact was measured using an automatic specific gravity meter (DMA-220H type, manufactured by Shinko Denshi Co., Ltd.), and the average value of 15 pieces was shown as the density of the compact (D1). The theoretical density (D2) of the compact was calculated from the density of silicon, the density of silicon nitride, and the ratio of silicon and silicon nitride in the raw material powder. The porosity was then calculated from the following formula. Porosity (R) (%)=(1-D1 / D2)×100

[0052] (5) Bulk density The above-mentioned green body density (D1) was defined as the bulk density of the green body.

[0053] (6) Beta conversion rate Powder X-ray diffraction (XRD) measurements were performed using CuKα radiation, and the weight ratios of the α and β phases in the silicon nitride powder were calculated by the method described in C.P. Gazzara and D.R. Messier: Ceram. Bull., 56 (1977), 777-780.

[0054] (7) BET specific surface area The specific surface area of ​​the produced silicon nitride powder was measured by the BET method specific surface area measurement device (Macsorb HM model-1201) manufactured by Mountec Co., Ltd., using the BET single point method by nitrogen gas adsorption. Prior to carrying out the above-mentioned specific surface area measurement, the silicon nitride powder to be measured was heat-treated in air at 600° C. for 30 minutes to remove any organic matter adsorbed on the powder surface.

[0055] (8) Aluminum and iron content The impurity concentration in silicon powder was measured as follows. The silicon powder to be subjected to the combustion synthesis reaction was weighed out into a resin container, and 70% high-purity concentrated nitric acid was added. Carefully, 50% high-purity hydrofluoric acid was added dropwise, taking care not to make the silicon decomposition reaction too vigorous, until the silicon powder was completely dissolved. The mixed acid of nitric acid and hydrofluoric acid remaining in the resin container was then completely evaporated on a hot plate, and the heavy metal components adsorbed on the inner surface of the resin container were recovered with 1% dilute nitric acid, and the heavy metal components were quantified using an inductively coupled plasma atomic emission spectrometer (ICP-AES). Here, an iCAP 6500 DUO (manufactured by Thermo Fisher Scientific) was used. The impurity concentrations in the silicon nitride powder were measured using the method specified in JIS R 1603:2007.

[0056] (9) Preparation of sintered body To 100 parts by mass of silicon nitride powder as a sample, 5 parts by mass of yttria powder as a main sintering aid and 2 parts by mass of alumina powder or magnesia powder as a secondary sintering aid were added, and mixed thoroughly in ethanol using a planetary ball mill. After thoroughly drying the silicon nitride powder mixed with the sintering aid in this way, about 20 g was added to a 0.2 ton / cm 2 Each piece was sealed in a soft rubber bag and placed in water, and a pressure of 2 tons / cm was applied to the surface of the molded body. 2 CIP treatment was performed so that a pressure of 1000 MPa was applied. The surfaces of the disk-shaped compacts that had been subjected to CIP treatment were coated with boron nitride powder to prevent adhesion. The compacts were stacked in groups of five in a highly airtight box-type setter made of boron nitride, and sintered at 1900°C for five hours in a nitrogen atmosphere of 0.8 MPa to obtain sintered compacts.

[0057] (10) Density of sintered body The density of each sintered body was measured using an automatic specific gravity meter (DMA-220H type, manufactured by Shinko Denshi Co., Ltd.), and the average value of 15 pieces was shown as the density of the sintered body.

[0058] (11) Thermal conductivity of sintered body (W / m K) The thermal diffusivity of each sintered body was measured using a laser flash thermal property measuring device (Kyoto Electronics Manufacturing Co., Ltd.: LFA-502). Thermal conductivity is calculated by multiplying the thermal diffusivity, the sintered body density, and the sintered body specific heat. The specific heat of the silicon nitride sintered body was set to 0.68 (J / g K). Three pieces were randomly selected from the 15 pieces of sintered bodies prepared by the method in (9) above, and test pieces for measuring thermal properties by the laser flash method were cut out. The thermal conductivity of each of the three test pieces was calculated from the density and thermal diffusivity, and the average value of the thermal conductivities of the three test pieces was shown as the thermal conductivity of the sintered body.

[0059] (12) Three-point bending strength of sintered body (MPa) Ten pieces were randomly selected from the 12 pieces produced by the method (9) above, excluding the three pieces used for the thermal conductivity measurement, and cut out to obtain test pieces for measuring the three-point bending strength. The three-point bending strength of each of the 10 test pieces was measured using a method conforming to JIS R 1601:2008. A test jig with a support distance of 30 mm was used. The average value of the three-point bending strengths of the 10 test pieces was shown as the three-point bending strength of the sintered body.

[0060] In the following experiments, the following raw powders were used: Silicon powder High-purity polycrystalline silicon of solar cell grade was pulverized to an average particle size of about 5 μm using an airflow pulverizer (jet mill) lined with silicon nitride, and 100% silicon powder was obtained and used as raw material powder A. The oxygen content of the silicon powder obtained here was about 0.3% by mass. The impurity contents were 10 ppm for Fe and 5 ppm for Al. Silicon nitride powder (diluent) Silicon nitride powder with an average particle size of 1 μm was used.

[0061] <Example 1> A raw material powder was prepared by mixing 8 kg of silicon powder and 2 kg of silicon nitride powder. The prepared raw material powder was pressurized and molded using a commercially available powder molding die to produce a molded body. Specifically, a powder molding die with an inner dimension of 50 mmφ was used, and about 30 g of the raw material powder was filled into the powder molding die, and then a pressure of about 60 kg / cm was applied from the top surface. 2 After compressing the mixture at a pressure of 1000 MPa, a cylindrical compact with an inner dimension of 50 mmφ and a height of approximately 15 mm was taken out of the cylindrical container. Several compacts were produced in the same manner. Then, the compacts were stacked flat in the reaction container as shown in Figure 3(a). In addition, inside the reaction vessel, a heat insulating layer was formed by using silicon nitride powder so as to fill the gaps between the arranged molded bodies and to cover the upper surfaces with a thickness of 30 mm. After the molded body was placed in the reaction vessel as described above, it was placed in a pressure-resistant closed reactor equipped with an ignition device and a gas supply / exhaust mechanism, and the pressure in the reactor was reduced to degass, and then nitrogen gas was supplied to replace the nitrogen. Nitrogen gas was then gradually supplied until the pressure was increased to 0.7 MPa. Then, the end of one of the molded bodies in the reaction vessel was ignited, and a combustion synthesis reaction was carried out to obtain lump silicon nitride. The surface of the lump silicon nitride was then brushed to remove the black unreacted silicon from the lump silicon nitride. The lump silicon nitride was then crushed to about 5 to 20 μm by rubbing against each other, and then an appropriate amount was put into a vibration mill and finely pulverized for 7 hours. The fine pulverizer and fine pulverization method used were of the usual type, but the inside of the pulverizer was lined with urethane as a measure to prevent heavy metal contamination, and balls mainly made of silicon nitride were used as the pulverization media. Also, 1 mass% of ethanol was added as a pulverization aid just before the start of pulverization, and the pulverizer was sealed to perform pulverization. As a result, the average particle size was 0.7 μm, the specific surface area was 16 m 2 A silicon nitride powder containing substantially 100% β-type silicon nitride and having a molecular weight of 1000 g was obtained. The reaction conditions and the physical properties of the resulting silicon nitride powder are shown in Table 1.

[0062] [Sintered body 1] 5 parts by mass of yttria as a main sintering aid and 2 parts by mass of magnesia as a secondary sintering aid were added to 100 parts by mass of the silicon nitride powder obtained by the above method, and mixed in a planetary ball mill. After undergoing the above-mentioned uniaxial press molding and CIP molding, the mixture was fired at 1900°C for 5 hours in a nitrogen atmosphere of 0.8 MPa. The density of the obtained sintered body was 3.25 g / cm 3 The thermal conductivity was 90 W / m·K, and the three-point bending strength was 750 MPa. The sintered body of this silicon nitride powder had a high density and was very dense, and also had excellent thermal conductivity and bending strength properties.

[0063] <Example 2> In the method for producing silicon nitride powder of Example 1, the porosity of the molded body was set to a low value as shown in Table 1, and a combustion synthesis reaction was carried out to obtain chunky silicon nitride. The obtained silicon nitride agglomerates were disintegrated and finely pulverized under the same conditions as in Example 1. As a result, a silicon nitride powder consisting essentially of 100% β type and having the properties shown in Table 1 was obtained.

[0064] [Sintered body 2] Using the above silicon nitride powder, a sintered body was produced under the same conditions as for sintered body 1 in Example 1. The properties of the sintered body were as excellent as those of sintered body 1.

[0065] <Example 3> In the method for producing silicon nitride powder in Example 1, the porosity of the molded body was set to a relatively high value as shown in Table 1, and the combustion synthesis reaction was carried out while lowering the pressure during the reaction, and silicon nitride powder was synthesized in the same manner as in Example 1. As a result, the silicon nitride powder obtained was β-type silicon nitride containing about 5% α-type. The properties of the obtained silicon nitride powder are shown in Table 1.

[0066] [Sintered body 3] Using the silicon nitride powder containing the α-type, a sintered body was produced under the same conditions as for sintered body 1 in Example 1. The properties of the sintered body were as excellent as those of sintered body 1.

[0067] <Example 4> A silicon nitride powder was obtained in the same manner as in Example 1, except that the fine pulverization time was shortened to 5 hours in the method for producing a silicon nitride powder shown in Example 1. The properties of the obtained silicon nitride powder are shown in Table 1.

[0068] [Sintered body 4] Using the silicon nitride powder obtained by the above method, a sintered body was produced under the same conditions as for sintered body 1 in Example 1. The properties of the sintered body were as excellent as those of sintered body 1 above.

[0069] <Example 5> Silicon nitride powder was obtained in the same manner as in Example 1, except that the fine pulverization time was extended to 10 hours in the method for producing silicon nitride powder shown in Example 1. The properties of the obtained silicon nitride powder are shown in Table 1.

[0070] [Sintered body 5] Using the silicon nitride powder obtained by the above method, a sintered body was produced under the same conditions as for sintered body 1 in Example 1. The properties of the sintered body were as excellent as those of sintered body 1 above.

[0071] <Example 6> Except for changing the ratio of silicon powder and silicon nitride powder in the raw material powder, the combustion synthesis reaction and pulverization method were carried out in the same manner as in Example 1. The properties of the obtained silicon nitride powder are shown in Table 1.

[0072] [Sintered body 6] Using the silicon nitride powder obtained by the above method, a sintered body was produced under the same conditions as for sintered body 1 in Example 1. The properties of the sintered body were as excellent as those of sintered body 1 above.

[0073] <Comparative Example 1> Except for the fact that the raw material powder was not molded but was directly charged into the reaction vessel, the combustion synthesis reaction and pulverization method were carried out in the same manner as in Example 1. The properties of the obtained silicon nitride powder are shown in Table 1.

[0074] [Sintered body 7] Using the above silicon nitride powder, a sintered body was produced under the same conditions as for sintered body 1 in Example 1. The properties of the sintered body were as excellent as those of sintered body 1.

[0075] <Comparative Example 2> Except for the fact that the raw material powder was not molded but was directly charged into the reaction vessel, the combustion synthesis reaction and pulverization method were carried out in the same manner as in Example 4. The properties of the obtained silicon nitride powder are shown in Table 1.

[0076] [Sintered body 8] Using the above silicon nitride powder, a sintered body was produced under the same conditions as for sintered body 4 in Example 4. The properties of the sintered body were as excellent as those of sintered body 1 above.

[0077] <Comparative Example 3> Except for the fact that the raw material powder was not molded but was directly charged into the reaction vessel, the combustion synthesis reaction and pulverization method were carried out in the same manner as in Example 5. The properties of the obtained silicon nitride powder are shown in Table 1.

[0078] [Sintered body 9] Using the above silicon nitride powder, a sintered body was produced under the same conditions as for sintered body 5 of Example 5. The properties of the sintered body were as excellent as those of sintered body 1 above.

[0079] <Comparative Example 4> Except for the fact that the raw material powder was not molded but was directly charged into the reaction vessel, the combustion synthesis reaction and pulverization method were carried out in the same manner as in Example 6. The properties of the obtained silicon nitride powder are shown in Table 1.

[0080] [Sintered body 10] Using the above silicon nitride powder, a sintered body was produced under the same conditions as for sintered body 6 of Example 6. The properties of the sintered body were similar to those of sintered body 1 above.

[0081] [Table 1]

[0082] Comparative Example 5 In the method for producing silicon nitride powder in Example 1, the combustion synthesis reaction was carried out with the porosity of the compact set to a value of 30%. In this case, the combustion reaction did not proceed sufficiently, and a fire broke out during the reaction, resulting in a large amount of unreacted material.

[0083] Comparative Example 6 In the method for producing silicon nitride powder in Example 1, the porosity of the molded body was set to a value of 80%. In this case, the molded body was brittle, which made it difficult to handle and place it in a reaction vessel.

[0084] It was found that powdering can be suppressed and the nitride recovery rate can be improved by using a raw material that has been molded to a predetermined porosity. It was also found that even when molded raw material is used, an excellent sintered body can be obtained, just like when unmolded raw material is used. In addition, black streaky unreacted silicon remained on the surface of the silicon nitride block produced using unmolded raw material. From the streaky shape, it is considered that the remaining unreacted silicon is caused by cracks that occurred in the filled raw material powder. Since the cracks reach deep positions from the surface of the raw material powder, it is considered that unreacted silicon remained deep from the surface of the silicon nitride block in the silicon nitride block produced using the unmolded raw material. And, it is considered that the nitride recovery rate was low in the silicon nitride block produced using the unmolded raw material, since the unreacted silicon could not be removed from the silicon nitride block unless the surface of the silicon nitride block was scraped off considerably by brushing. Furthermore, by forming a heat insulating layer around the molded raw material, it was possible to reduce the amount of unreacted material to 10% or less, and in some cases to 5% or less. [Explanation of symbols]

[0085] 1A~1C Molded body 2 Heat-resistant container 3. Insulation layer

Claims

1. A method for synthesizing a nitride of a metal by igniting a raw material powder containing a metal powder contained in a reaction vessel under a nitrogen atmosphere and propagating the nitriding combustion heat of the metal powder throughout the contained raw material powder, the method comprising the steps of: preparing a plurality of compacts made of the raw material powder and having a porosity of 40 to 70%, and containing the plurality of compacts in the reaction vessel such that the distance between the adjacent compacts is within 10 mm.

2. 2. The method for producing a metal nitride according to claim 1, wherein the raw material powder contains 0 to 80 parts by mass of a metal nitride powder with respect to 100 parts by mass of the metal powder.

3. 3. The method for producing a metal nitride according to claim 1, wherein a plurality of compacts of the raw material powder are placed in the reaction vessel in contact with one another.

4. A method for producing a metal nitride as described in claim 1 or 2, wherein each of a plurality of compacts of the raw material powder are molded into a shape that allows for surface contact, and are placed in the reaction vessel in surface contact with each other.

5. The method for producing a metal nitride according to any one of claims 1 to 4, wherein a heat insulating layer made of a material that is nitrogen permeable and inactive to a nitriding reaction is formed and adhered to an upper surface of the compact of the raw material powder contained in the reaction vessel.

6. The method for producing a metal nitride according to any one of claims 1 to 5, wherein the metal is silicon.

Citation Information

Patent Citations

  • Printer unit

    JP1981027441A

  • Production of silicon nitride fine powder

    JP1987162608A

  • Combustion synthesis of high-purity tin

    JP1992124007A

  • Silicon nitride powder and slurry and filler using the silicon nitride powder

    JP2000128511A

  • Production of boron nitride, aluminum nitride or silicon nitride through combustion synthesis

    JP2000264608A